Comparación entre diseños optimizados y diseños reales en redes de distribución de agua potable : efecto del aumento de la población a lo largo de la vida útil del proyecto (2017)
Population growth in cities exposes WDS to operating conditions that violate hydraulic parameters such as minimum network pressure. Due to the above, it is necessary to establish methodologies for the rehabilitation of these WDS that guarantee the hydraulic requirements and provide optimum results in terms of costs. This work explores the viability of a rehabilitation methodology based on the Resilience Index and the Specific Power criteria when comparing the results obtained with these parameters with the optimal design of WDS with the OPUS methodology. The results of six WDS case studies from different regions of Colombia are analyzed in terms of costs and hydraulic parameters, obtaining better results using the Resilience Index parameter in the methodology.--Tomado del Formato de Documento de Grado.